Full-day School Application and Its Effect on Character Building of Students (Case Study at Elementary School Nasima Semarang) - Nurkholis, Indra; Masrukhi, Masrukhi; Juhadi, Juhadi (JESS (Journal of Educational Social Studies), 2018)
Implementation of character education through the concept of full-day school in Semarang City has not been much implemented, this is due to inadequate infrastructure, costs and human resources. The purpose of this study was to analyze the influence of character values ​​on the application of the concept of full-day school in Elementary School Nasima. This research was conducted qualitatively, with a case study approach. Data and information are obtained from informants and documents. Data collection techniques for interviews, observations, and documentation studies; then analyzed qualitatively. The results of the study showed that the positive influence of the application of full-day school was applied in schools. The negative effect of the application of full-day school is that students have higher physical and psychological burdens compared to public schools, because of the relatively high demands on academic achievement.